Mediating Human-Technology Relationships: Explorations of Hybridity, Humanity and Embodiment in Doctor Who - Anne Cranny-Francis (University of Edinburgh, 2009)
The relationship between human beings and technology has been a regular concern of the television series, Doctor Who. Though its titular hero moves through space-time by means of advanced technology and he is by his own admission a technological genius and Doctor 'of everything really', the program nevertheless consistently maps the unease that attends the interaction of humans and the technology - whether through the human characters' horror at the abuse of technology and its power or through characters who incorporate this interaction.